Breast cancer metastasis in sellar and suprasellar region. A rare presentation, and the ideal clinical management - Tiago Holanda; Isnara Mara Freitas Pimentel; Lucas Alverne Freitas de Albuquerque (Interdisciplinary Neurosurgery, 2024)
Background: Breast cancer is the more common tumor in women. The first description date 1789 by Mr. Hughes described a case of breast cancer of a 44-year-old married woman. The advances in the treatment of the pathology led to a higher life expectancy and increased the frequency of brain metastasis since 1970. The symptoms depend on the brain region committed. The cerebral lobes and cerebellum are more commonly affected, and the treatment is based on a triple basis: microsurgery, radiotherapy/radiosurgery, and the control of the extracerebral disease. The sellar region is a rare location. Only 38 cases were previously reported. Case report: A 50-year-old woman presented progressive visual impairment, headache, and a past clinical history of breast cancer. Radiological exams showed an expansive lesion occupying the sella turcica, the suprasellar, and the pre-sellar spaces. An endoscopic endonasal biopsy was performed and confirmed Breast Cancer metastasis. Conclusion: Despite the uncommon site, the sella turcica must be remembered as a possible site of breast cancer metastasis. The previous history of the oncological disease, the atypical radiologic aspect, and the fast and progressive onset of the symptoms are important aspects to be analyzed during medical management.